2022
DOI: 10.1109/jbhi.2022.3205058
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Neurodegenerative Diseases From Gait Rhythm Through Time Domain and Time-Dependent Spectral Descriptors

Abstract: The analysis of gait rhythm by pattern recognition can support the state-of-the-art clinical methods for the identification of neurodegenerative diseases (NDD). In this study, we investigated the use of time domain (TD) and time-dependent spectral features (PSDTD) for detecting NDD sub-types. Also, we proposed two classification pathways for supporting NDD diagnosis, the first one made by a two-step learning phase, whereas the second one encompasses a single learning model. We considered strideto-stride fluctu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Concurrently, recent studies involving individuals with neurodegenerative pathologies have revealed recurrent temporal and kinematic alterations during gait compared with healthy subjects [54,55]. In this context, a deeper understanding of the effects of FES on a healthy population could serve as a robust foundation for developing biotechnological solutions aimed at mitigating the adverse effects observed during the gait of individuals with neurodegenerative diseases.…”
Section: Applications Perspectives and Limitationsmentioning
confidence: 96%
“…Concurrently, recent studies involving individuals with neurodegenerative pathologies have revealed recurrent temporal and kinematic alterations during gait compared with healthy subjects [54,55]. In this context, a deeper understanding of the effects of FES on a healthy population could serve as a robust foundation for developing biotechnological solutions aimed at mitigating the adverse effects observed during the gait of individuals with neurodegenerative diseases.…”
Section: Applications Perspectives and Limitationsmentioning
confidence: 96%
“…In this study, three state-of-the-art classification algorithms were used for myoelectric control: linear discriminant analysis (LDA), support vector machine (SVM), and K-nearest neighbours (KNN) [1,4,36]. Concerning the LDA, it is a statistical learning model that has demonstrated applicability in myoelectric hand gesture recognition [1,3,37].…”
Section: Classification Algorithmsmentioning
confidence: 99%
“…A further step for the next-generation exercises apps would be to integrate clinical and rehabilitative intelligence assessment systems, by using modern wearable devices and new Machine Learning (ML) algorithms. This would enable to gather additional clinical data, such as those related to disease severity and its progressions, and to perform clinical assessments, for example those related to mobility, thus helping clinicians to provide optimal care even at patients’ home ( 52 , 53 ). Increasing and improving the quality of clinical data collection would help clinicians to provide optimal care even at patients’ home and it might promote the creation of extensive datasets useful for the growth of new patient-centered model of care ( 54 ).…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%